2014
DOI: 10.1021/am502411y
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Integrated Design for Enhanced Cathodes of Ni Foam-Supported Pt/Carbon Nanotubes for Li-O2 Batteries

Abstract: Designing an effective microstructural cathode combined with a highly efficient catalyst is essential for improving the electrochemical performance of Li-O2 batteries (LOBs), especially for long-term cycling. We present a nickel foam-supported composite of Pt nanoparticles (NPs) coated on self-standing carbon nanotubes (CNTs) as a binder-free cathode for LOBs. The assembled LOBs can afford excellent electrochemical performance with a reversible capacity of 4050 mAh/g tested at 20 mA/g and superior cyclability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 48 publications
1
43
0
Order By: Relevance
“…Based on initial charge-discharge behaviors, a comparison of ORR and OER showed that PtRu/C possessed lower overpotentials for charging and discharging than PtPd/C and PtIr/C, in which the capacity followed an order: PtRu/C (~ 346 mAh g −1 ) > PtPd/C (~ 153 mAh g −1 ) > PdIr/C (~ 135 mAh g −1 ). Table 2 shows the electrochemical performances for typical noble metal-carbon composite bifunctional catalysts as cathodes in MABs [86,87,89,91,92,96,100,104].…”
Section: Composites Of Carbon and Other Noble Metals Or Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on initial charge-discharge behaviors, a comparison of ORR and OER showed that PtRu/C possessed lower overpotentials for charging and discharging than PtPd/C and PtIr/C, in which the capacity followed an order: PtRu/C (~ 346 mAh g −1 ) > PtPd/C (~ 153 mAh g −1 ) > PdIr/C (~ 135 mAh g −1 ). Table 2 shows the electrochemical performances for typical noble metal-carbon composite bifunctional catalysts as cathodes in MABs [86,87,89,91,92,96,100,104].…”
Section: Composites Of Carbon and Other Noble Metals Or Alloysmentioning
confidence: 99%
“…For example, composite catalysts such as PtCo 2 /C [89] and Pt/CNTs/Ni [104] can deliver high discharge capacities of 3040 and 4050 mAh g −1 for MABs, respectively. Compared to pure Pt catalysts, other noble metals (e.g., Ir or Ru) are also able to increase OER favoring cycling performances.…”
Section: Composites Of Carbon and Other Noble Metals Or Alloysmentioning
confidence: 99%
“…Typically, the loading density has a strong effect on cycle performance of Li-air battery, because the cycling time is calculated based on loading amount as well as current density. Therefore, control the loading amount of catalysts is necessary to compare with other research results (in fact, most of results were achieved in high current density with a catalyst loading of 0.5 mg cm À2 or low current density with a catalyst loading of 1.0 mg cm À2 ) [23,34,35]. In this study, the Liair cell with 0.5 mg cm À2 of catalyst loading was cycled at a current density of 0.2 mA cm À2 with a limited capacity of 1000 mAh g À1 .…”
Section: Resultsmentioning
confidence: 99%
“…Various types of materials including metals, [122][123][124] metal oxides, [125][126][127][128] and transition bimetallic nitrides, [ 129,130 ] have been investigated. The charge voltage of the Li-O 2 battery with these catalysts is lowered to some extent, which can benefi t the chemical stability enhancement of carbon cathode.…”
Section: Lowered Charge Voltagementioning
confidence: 99%